Interpolation methods for creating a scatter radiation exposure map (Brazilian Journal of Radiation Sciences (BJRS), 2019)
A well know way for best understanding of radiation scattering and radiation exposure rate during a procedure using ionizing radiation is to map exposure over the space around the source and sample. This map is done measuring exposure in points regularly spaced, it means, measurement will be placed in localization chosen by increasing a regular steps from a starting point, along the x, y and z axes or, in more efficient way, radial and angular coordinates. However, it is not always possible to maintain the accuracy of the steps throughout the entire space, or there will be regions of difficult access where the regularity of the steps will be impaired. In this work we use a high energy radiation source to simulate a common radiography setup and construct its exposure map. The arrangement of the points and the interpolation were used considering polar coordinates. Then with the same data, an interpolation using the Delaunay triangulation was made. The results show the advantages and disadvantages of each other besides the high coherence for the same data. To simulate the impossibility of regular points, the same procedures were performed in the absence of any point and compared. The results show a lower total variation when the map is calculated by triangulation. The computational and graphic treatment was performed with GNU OCTAVE software and its image processing package. The data were acquired from a bunker where a 6MeV betatron was used as a primary source. A well know way for best understanding of radiation scattering and radiation exposure rate during a procedure using ionizing radiation is to map exposure over the space around the source and sample. This map is done measuring exposure in points regularly spaced, it means, measurement will be placed in localization chosen by increasing a regular steps from a starting point, along the x, y and z axes or, in more efficient way, radial and angular coordinates. However, it is not always possible to maintain the accuracy of the steps throughout the entire space, or there will be regions of difficult access where the regularity of the steps will be impaired. In this work we use a high energy radiation source to simulate a common radiography setup and construct its exposure map. The arrangement of the points and the interpolation were used considering polar coordinates. Then with the same data, an interpolation using the Delaunay triangulation was made. The results show the advantages and disadvantages of each other besides the high coherence for the same data. To simulate the impossibility of regular points, the same procedures were performed in the absence of any point and compared. The results show a lower total variation when the map is calculated by triangulation. The computational and graphic treatment was performed with GNU OCTAVE software and its image processing package. The data were acquired from a bunker where a 6MeV betatron was used as a primary source.